(untitled) (Plant Tissue Culture and Biotechnology, 2022)
The world’s most expensive wood, sandalwood (Santalum album L.), requires a stringent mass-propagation technique to prevent future scarcity. Plant tissue culture is an efficient method that regenerates the whole plant from a single cell on a hormone-based growth medium. To efficiently regulate the formation of plants, it is important to understand the developmental organogenesis pathways (i.e., direct and indirect) through gene expression studies. Therefore, an effective protocol for the direct and indirect organogenesis of sandalwood was developed, followed by the characterization of gene expression patterns in investigation. Five in vitro organogenesis genes namely, Alternative oxidase (ao), Late embryogenesis abundant (lea), Cytochrome p450 (cyt-p450), ABC transporter (abct), and Serine-threonine phosphatase (stp), were screened from three stages of sandalwood development; (1) inoculated leaf, (2) proliferated leaf shoot/callus formation and (3) shoot formation. The best treatments for plant regeneration in Woody Plant Media (WPM) were SI24 (2.5 mg/l 2,4-D) for indirect organogenesis and SD14 (2.0 mg/l BAP and 0.4 mg/l-1 NAA) for direct organogenesis. During the initial stages of organogenesis, ao, cyt-p450 and abct showed no/little change in expression in the direct pathway however up-regulation of ao and abct and downregulation of cyt-p450 were observed in the indirect pathway. Expression of lea was increased up to 70-fold during direct and dropped to half during indirect organogenesis. The optimization of the sandalwood organogenesis regeneration medium and the identification of distinct gene expression patterns will serve as transcriptional markers for the early prediction of the organogenesis stage, assisting in the sandalwood conservation. Plant Tissue Cult. & Biotech. 32(2): 103-113, 2022 (December)